THE ANALYSIS OF STUDENTS’ DIFFICULTIES AND STRATEGIES USED IN ENGLISH TRANSLATION PROCESS - Maiya Lucito (JETLi: Journal of English Teaching and Linguistics, 2020)
This research is entitled “The Analysis of Students? Difficulties and Strategies Used in English Translation Process”. It can be seen that this is the qualitative research and the aims of this research are to know the methods used, the difficulties faced, and the strategies used by students in translation process. The researcher used two instruments, namely test and interview. The population of this research was the fourth semester students who had taken translation I in the third semester in English Language Education of Ar-Raniry State Islamic University. The sample was unit 1 consisting of 15 students. They were selected by using purposive sampling based on preliminary interview with translation lecturer. From the result of this research, it was found that there were 2 dominant methods that were used by participants in translation process, there are as follows: word-for-word translation and free translation method. In word-for-word translation, there were 9 participants (participant 1, 2, 4, 8, 9, 10, 11, 13, and 14) translated into the target language by single word in most common meaning and did preliminary translation (pre-translation) word for word. On the other hand, there were 6 participants (participant 3, 5, 6, 7, 12, 15) used free translation. They translated the text more clearly. The students faced many difficulties in religious culture in translation process. The difficulties they got from religious culture were vocabularies and terminologies. Moreover, participants were seldom found the religious vocabularies when they read and learned the common text. To overcome these difficulties in translation process, there were only 2 strategies mostly used by the participants in translation process. They were as follows: translation by a more general word and translation by paraphrase using related word. It was easy to understand the content of the text when they used both of translation strategies.